Variation of Cicer Germplasm to Manganese Toxicity Tolerance - Pradeep, Karthika; Bell, Richard W.; Vance, Wendy (Frontiers in Plant Science, 2020)
After aluminium, manganese toxicity is the most limiting factor for crops grown in acidic soils worldwide. But overall, research on Mn toxicity is still limited. The poor acid tolerance of chickpea may be related to Mn toxicity but there is no previous screening of chickpea germplasm for Mn toxicity tolerance nor in its wild Cicer relatives, Cicer reticulatum and Cicer echinospermum. A screening technique was developed for Mn toxicity tolerance using three released cultivars of chickpea (Cicer arietinum L): Ambar, PBA HatTrick, PBA Striker, one accession each of Cicer reticulatum and Cicer echinospermum, and lupin (Lupinus angustifolius) as a Mn-tolerant check, with 8 Mn concentrations, 2, 25, 50, 100, 150, 200, 250 and 500 M Mn as MnSO4 in a low ionic strength nutrient solution. The plants were harvested at 14 and 28 days after Mn treatments. The best discrimination into tolerant and intolerant Cicer genotypes based on relative shoot dry weight, root dry weight, total root length and scoring of toxicity symptoms was achieved at 150 M Mn after 14 days growth in Mn solution. Among the chickpea cultivars, the greater relative plant growth (both shoot and root) of Ambar and PBA Striker at 100 to 200 M Mn contrasted with PBA HatTrick, while the C. echinospermum accession was more tolerant to Mn toxicity than C. reticulatum. Manganese tolerance in both domestic and wild accession was associated with greater uptake of Mn and translocation of Mn from roots to shoots, and their internal tolerance to excess Mn.